2004
DOI: 10.7547/0940239
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressures in Rheumatoid Arthritis Using Prefabricated Metatarsal Padding

Abstract: 239Patients with established rheumatoid arthritis often bear a disproportionate amount of body weight over the metatarsal heads. 1 As joint deformity progresses, the plantar fat pad may be displaced, with a loss of cushioning of the forefoot and associated metatarsalgia. 2 Abnormal gait with reduced mobility may ensue with the development of pressure lesions, a splay forefoot, and bursae formation. [3][4][5][6][7] Management of the deformed rheumatoid arthritis foot includes conservative and surgical intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 35 publications
2
61
0
4
Order By: Relevance
“…One RCT (23) and 3 observational studies (28,29,31) investigated forefoot plantar pressure. Three of the 4 studies showed significant results for custom orthoses decreasing forefoot plantar pressure.…”
Section: Foot Function Three Rcts Investigated Foot Functionmentioning
confidence: 99%
“…One RCT (23) and 3 observational studies (28,29,31) investigated forefoot plantar pressure. Three of the 4 studies showed significant results for custom orthoses decreasing forefoot plantar pressure.…”
Section: Foot Function Three Rcts Investigated Foot Functionmentioning
confidence: 99%
“…They are also broadly used as a screening tool for diabetic patients to establish the risk of ulceration 17,18) . Plantar pressure evaluation is also used to assess the effectiveness of footwear 19,20) and orthotic interventions 21,22) . Despite the growing use of plantar foot pressure assessments for research and clinical purposes, the factors that contribute to loading patterns of the foot remain poorly understood 23) .…”
Section: Introductionmentioning
confidence: 99%
“…The orthotic devices were heat-moulded to the patient's foot while using the functional suspension subtalar joint neutral position technique [16,17]. Based on the findings of the podiatrist, functional corrections [9][10][11]16] (i.e. varus-, valgus corrections, metatarsal bars and metatarsal domes) and shock absorbing padding could be added [10,16].…”
Section: Process For Designing Usual Care Fomentioning
confidence: 99%
“…Redistribution of plantar foot pressure, by creating a larger weight bearing area, is supposed to be one of the working mechanisms of FOs [9][10][11]. A recent systematic review showed FOs to be effective in reducing pain and high plantar forefoot pressures.…”
mentioning
confidence: 99%